Histone methyltransferase G9a promotes liver cancer development by epigenetic silencing of tumor suppressor gene RARRES3 - Wei, Lai; Chiu, David Kung-Chun; Tsang, Felice Ho-Ching; Law, Cheuk-Ting; Cheng, Carol Lai-Hung; Au, Sandy Leung-Kuen; Lee, Joyce Man-Fong; Wong, Carmen Chak-Lui; Ng, Irene Oi-Lin; Wong, Chun-Ming (Journal of hepatology, 2017)
[Display omitted] •G9a was frequently upregulated in human HCC and associated with HCC aggressiveness.•G9a promoted HCC growth and metastasis both in vitro and in vivo.•Upregulation of G9a in HCC was attributed to gene amplification and loss of miR-1.•G9a epigenetically silenced the expression of tumor suppressor gene RARRES3 in HCC.•Targeting G9a by small molecular inhibitors suppressed HCC growth. Hepatocellular carcinoma (HCC) is a major leading cause of cancer mortality worldwide. Epigenetic deregulation is a common trait of human HCC. G9s is an important epigenetics regulator however, its role in liver carcinogenesis remains to be investigated. Gene expressions were determined by RNA-Seq and qRT-PCR. G9a knockdown and knockout cell lines were established by lentiviral-based shRNA and CRISPR/Cas9 gene editing system. Tumor-promoting functions of G9a was studied in both HCC cell lines and nude mice model. The downstream targets of G9a were identified by RNA-Seq and confirmed by ChIP assay. The therapeutic value of G9a inhibitors was evaluated both in vitro and in vivo. We identified G9a as a frequently upregulated histone methyltransferase in human HCCs. Upregulation of G9a was significantly associated with HCC progression and aggressive clinicopathological features. Functionally, we demonstrated that inactivation of G9a by RNAi knockdown, CRISPR/Cas9 knockout, and pharmacological inhibition remarkably abolished H3K9 di-methylation and suppressed HCC cell proliferation and metastasis in both in vitro and in vivo models. Mechanistically, we showed that the frequent upregulation of G9a in human HCCs was attributed to gene copy number gain at chromosome 6p21. In addition, we identified miR-1 as a negative regulator of G9a. Loss of miR-1 relieved the post-transcriptional repression on G9a and contributed to its upregulation in human HCC. Utilizing RNA sequencing, we identified the tumor suppressor RARRES3 as a critical target of G9a. Epigenetic silencing of RARRES3 contributed to the tumor-promoting function of G9a. This study shows a frequent deregulation of miR-1/G9a/RARRES3 axis in liver carcinogenesis, highlighting the pathological significance of G9a and its therapeutic potential in HCC treatment. Lay summary: In this study, we identified G9a histone methyltransferase was frequently upregulated in human HCC and contributes to epigenetic silencing of tumor suppressor gene RARRES3 in liver cancer. Targeting G9a may be a novel approach for HCC treatment.